Study of State-Owned Enterprises (SOEs) Profitability in Indonesia 2012-2016 Period - Muhamad Fathul Muin; Amalia Kusuma Wardini; Jumadi Jumadi (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2020)
One of the purposes of the establishment of SOEs is to become a source of funding for the state. But unfortunately, the losses and potential bankruptcy is still a business challenge to date. Therefore, the aims of this research to analyze the SOEs’ financial performance and the factors that affected profitability.The analysis method used is panel data regression involving 118 financial data companies in the year of 2012-2016. The variables used consisted of return on assets (ROA), total asset growth (TAG), current ratio (CR), total assets turnover (TATO), and debt to equity ratio (DER).After eliminating the outlier data and use other statistical tests, a fixed-model effect (FEM) was obtained. Based on the analysis result, the effect of TAG, CR, and TATO is positive and significant on the ROA. Meanwhile, the effect of the DER is not significant on ROA. This model is able to explain the variation of the dependent variable of 92,40 percent.